Superlinear damped vibration problems on time scales with nonlocal boundary conditions - Wei, Yongfang; Bai, Zhanbing (Nonlinear Analysis: Modelling and Control, 2022)
This paper studies a class of superlinear damped vibration equations with nonlocal boundary conditions on time scales by using the calculus of variations. We consider the Cerami condition, while the nonlinear term does not satisfy Ambrosetti–Rabinowitz condition such that the critical point theory could be applied. Then we establish the variational structure in an appropriate Sobolev’s space, obtain the existence of infinitely many large energy solutions. Finally, two examples are given to prove our results.
Keywords: damped vibration; nonlocal boundary condition; Cerami condition; variational structure; critical point theory